Analisis Antara Wanprestasi Dengan Tekanan Target Laba Perusahaan Dalam Perjanjian Jual Beli Handphone Online - Afif Sukandi; Hawa Icha Sania Salma (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The development of information technology has created a significant shift in consumer behavior, especially in terms of purchasing goods online. Companies running online businesses tend to have profit targets that must be achieved. The pressure to achieve this target can give rise to business practices that may give rise to legal conflicts, including potential breaches in sales and purchase agreements. This research aims to analyze defaults that occur in buying and selling cellphones through online buying and selling. The method used is normative juridical. The research results found that profit target pressure cannot be used as an excuse to violate contractual obligations and consumer protection rights. This case study involves online cellphone buying and selling transactions. This transaction concerns the aspect of default when there is an imbalance between the profit targets agreed upon by both parties. This research aims to analyze the relationship between default and pressure on profit targets set in online cellphone sales and purchase contracts. The results of the research show that there is a significant relationship between default and pressure on profit targets set in online cellphone sales and purchase contracts. These findings can be a basis for entrepreneurs to improve the terms of their online mobile phone sales and purchase contracts and prevent defaults in the future.